ANALISIS TINGKAT LITERASI KEUANGAN SYARIAH PADA RUMAH TANGGA KELUARGA NELAYAN DI KABUPATEN TANJUNG JABUNG BARAT - Puja Aprilia; Eja Armaz Hardi; Beid Fitrianova Andriani (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
So this study aims to determine the level of Islamic financial literacy in fisherman family housewives in Kampung Nelayan Village and to find out what are the obstacles in increasing Islamic financial literacy in Kampung Nelayan Village. This research qualitativemethod. The results of this study indicate that Islamic financial literacy in fisherman family housewives in Kampung Nelayan Village is not literate for aspects of basic Islamic financial knowledge of 22.4%, in terms of aspects of Financial Behavior it is in the less literate category which is equal to 46%, then from the aspect of Attitude Islamic finance is also in the less literate category, namely 28.8%. The obstacles in increasing Islamic financial literacy in Kampung Nelayan Village are the lack of socialization and knowledge education related to Islamic financial literacy and the absence of cooperation between Kampung Nelayan Village and Financial Institutions and the Financial Services Authority or related parties.